Periodontal disease and respiratory disorders - K., Malathi; S, sujatha (International Journal of Dental Research, 2013)
The oral cavity has a multitude of functions in relation to daily life. The poor health has the potential of affecting the quality of life. In recent years, efforts have been made to recognize oral health as an integral part of overall health. There is a fair evidence exists between respiratory disorders and poor oral hygiene & good evidence exist that improved oral health and professional oral health care reduce the progression or occurrence of respiratory diseases among high risk adults. This paper discusses the relation between the periodontitis and its influence on the incidence of respiratory disorders.